PERANAN ANALISA LAPORAN KEUANGAN DALAM EFEKTIFITAS PENILAIAN PERMOHONAN KREDIT - Hidayah, Riya; Nasution, Ute Chairuz; Muljati, Diana Juni (Jurnal Dinamika Administrasi Bisnis, 2015)
A company applyin fr a lan then the bank should conductan analysis of the financial statements in an effort to support the effectiveness f the loan application assessment. Financial statementÂ  analysis conducted by the bank assessed using ratios include liquidity ratio, solvency and profitability ratios. The ratio analysis used by the bank to assess the financial condition of a company that will apply for the credit in deciding whether a loan application is accepted or rejected. By using secondary data from the annual financial statement for the period of three years. Quantitative descriptive method by which data is obtained in the from of figures. In this study were collected and analyzed based on predefined criteria to determine the factors that can support the efeectiveness of the loan application assessment with financial statement analysis. Â Keyword :financial statement, the effectiveness of the loan application appraisal.